Endodermal sinus tumor of vagina posing a diagnostic challenge and managed by chemotherapy and novel posterior sagittal surgical approach: Lessons learned. Issue 2 (7th October 2013) - Goyal, Surbhi; Puri, Archana; Mishra, Kiran; Aggarwal, Satish Kumar; Kumar, Manisha; Sonaker, Pitamber
Abstract Vaginal germ cell tumor (GCT) is a rare gynecological malignancy with no more than 100 reported cases in the international medical literature. It is an unusual, but an important, cause of premenarchal vaginal bleeding in a child. This article describes a 2‐year‐old child with vaginal GCT, initially misdiagnosed as rhabdomyosarcoma (on imprint smear cytology) and then as clear cell adenocarcinoma. The authors highlight the salient differentiating clinical, radiological and histological features to prevent misdiagnosis in future. The report emphasizes the need for increased awareness and screening for vaginal GCT by estimation of serum α‐fetoprotein levels, in all patients with premenarchal vaginal bleeds, to prevent inadvertent operative interventions.